An optimization framework for dstributed energy resource planning and energy management strategy of storage devices and electric vehicles - CEYLAN, OĞUZHAN (My University, 2022)
© 2022 IEEE.This paper proposes an optimal coordination strategy for electric vehicles and energy storage devices in distribution grids besides the optimal allocation problem of renewable distributed generation (RDGs) and energy storage devices (ESDs). By finding the optimal number, size, and site of the RDGs and ESDs, together with the operation strategy of the ESDs and smart charging of a large number of EVs, the performance of the distribution grids will be improved. An advanced grey wolf optimization (AGWO) algorithm is used to minimize energy losses and voltage violations simultaneously in the test systems. Simulations are tested on IEEE 33 and 69 bus networks to find near-optimal solutions for the optimization problem. Based on the simulation results, the proposed optimization framework reduced the systems\" losses while minimizing the voltage violations by finding the optimal control parameters of the devices.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Yerbilimleri; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; COĞRAFYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; GEOSCIENCES; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; GEOGRAPHY; Elektrik ve Elektronik Mühendisliği; Fizik Bilimleri; Kontrol ve Optimizasyon; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Electrical and Electronic Engineering; Physical Sciences; Control and Optimization; Geography, Planning and Development; Social Sciences & Humanities; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; Distributed generation; electric vehicle charging management; Heuristics; Real power losses; storage systems; Distributed generation; storage systems; Heuristics; electric vehicle charging management; Real power losses